2018
DOI: 10.1016/j.ijhcs.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Deciding the different robot roles for patient cognitive training

Abstract: Alzheimer's Disease (AD) and Mild Cognitive Impairment (MCI) represent a major challenge for health systems within the aging population. New and better instruments will be crucial to assess the disease severity and progression, as well as to improve its treatment, stimulation, and rehabilitation. With the purpose of detecting, assessing and quantifying cognitive impairments like MCI or AD, several methods are employed by clinical experts. Syndrom Kurztest neuropsychological battery (SKT) is a simple and short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…In our previous framework [4], we already demonstrated that the HRI problem can be effectively modeled using PDDL, and that an off-the-shelf planner can be used then to manage the interaction between the robot and the patient. However, in this framework, the robot can provide assistance only based on the levels set up by the caregiver and it can switch from one level to the other (more assistive) only for wrong moves of the user.…”
Section: Adaptive Modulementioning
confidence: 99%
See 2 more Smart Citations
“…In our previous framework [4], we already demonstrated that the HRI problem can be effectively modeled using PDDL, and that an off-the-shelf planner can be used then to manage the interaction between the robot and the patient. However, in this framework, the robot can provide assistance only based on the levels set up by the caregiver and it can switch from one level to the other (more assistive) only for wrong moves of the user.…”
Section: Adaptive Modulementioning
confidence: 99%
“…It is worth mentioning that although this paper is mainly focused on the loop of interaction between the robot and the patient, in the general approach we rely heavily on the caregiver input (what we call the first loop of interaction) [4]. Thus, the presented work has been designed taking into account that caregivers and patients with dementia agree in receiving assistance from a robot [2].…”
Section: The Sorting Tokens Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Our use-case [11] is to develop a robotic system easy to configure from the caregiver (first loop of interaction). The robot can administer cognitive exercises based on the Syndrom-Kurztest (SKT), encouraging and motivating the user through speech and gestures (second loop of interaction).…”
Section: A Skt: the Cognitive Training Taskmentioning
confidence: 99%
“…In this paper, we build on our previous work [11], where a robot is endowed with the abilities to assist dementia patients during cognitive exercises (see Figure 1). In [11], we define two loops of interaction: the first one in which the caregiver sets the physical and mental user impairment and the initial robot behaviour; the second one in which the robot interacts with a patient using a hand-crafted policy and providing him with adaptive levels of assistance based on his performance, while he is playing a cognitive exercise. In this article, we extend this system by: i) providing an easy tool for the caregiver to set up the patient's profile through the concept of Persona (first loop of interaction) and ii) learning the robot initial policy (second loop of interaction).…”
Section: Introductionmentioning
confidence: 99%